Beyond the collaterals: Additional value of multiphase CTA in acute ischemic stroke evaluation. Issue 4 (August 2019) - Volders, D; Shewchuk, JR; Marangoni, M; Ni Mhurchu, E; Heran, MKS
Purpose: Multiphase computed tomography angiography (MP-CTA) is an innovative imaging tool that can give those managing acute ischemic stroke temporal information on degree and extent of pial collateral arterial filling in the affected brain. We sought to estimate the incidence of false-positive or -negative evaluation of the carotid bifurcation or intracranial thrombus on single-phase CTA (SP-CTA) compared with MP-CTA. Material and methods: A single-center, retrospective consecutive review was conducted of imaging and clinical records of 150 patients in two months who presented with neurological symptoms with a National Institutes of Health Stroke Scale score ≥ 2 and who received an MP-CTA as part of their investigative work-up. The cohort consisted of 52.3% male and 47.7% female patients. Median individual age was 68 years (interquartile range 60–79). Extracranial and intracranial vessel images of the initial early arterial phase were evaluated and compared with late arterial and early venous phase images. Results: In the cohort of 150 patients, in three patients (2%) SP-CTA would have led to an incorrect diagnosis and management without MP-CTA–acquired source imaging. The three scenarios represented differentiating a carotid string sign from internal carotid artery occlusion, determining the appearance and extent of thrombus in carotid T-occlusion, and differentiating slow flow and contrast mixing-related artifacts from intraluminal thrombus. Conclusions: In addition to improving assessment of collateral circulation in acute stroke patients, MP-CTA is also useful in assessing specific flow-related scenarios for which SP-CTA may give spurious results.